USM WILL ASSIST FLOOD VICTIMS, SAYS VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 5 January 2015 Universiti Sains Malaysia (USM) will assist about 300 of its staff affected by the recent floods in Kelantan and will participate in the postflood operations process in the state. Its ViceChancellor, Professor Dato' Dr. Omar Osman said in his office here, the university is seeking available funds to provide the much needed help to those affected to ease their burden.